Establishment of a suitable regeneration protocol for rapid propagation of Piper nigrum L. through in vitro culture - Raju, Md Raihan Iqbal; Junaki, Merina; Hossain, Mohd Talim (Jahangirnagar University Journal of Biological Sciences, 2023)
An experiment was performed to establish a suitable regeneration protocol for the rapid propagation of Piper nigrum L. using nodal segments and leaf tissues as explants through direct and indirect organogenesis. After surface sterilization, several types of explant were inoculated onto gelled MS medium containing various concentrations and combinations of growth regulators for callus and direct shoot induction. The highest callus induction frequency was 92% and 84% in the case of leaf tissues and nodal segments, respectively, in gelled MS medium containing 2.0 mg/l 2,4-D. Multiple shoots (6.43±0.35 shoots per unit callus) were obtained when the calli from both explant types were cultured on MS medium containing 1.0 mg/l BAP. Nodal segments showed the best result (85%) in terms of direct shoot induction in MS medium supplemented with 1.5 mg/l BAP, where the highest number of shoots per explant was 5.03±0.69. The directly induced shoots were multiplied and elongated on MS medium containing 1.0 mg/l BAP and 0.5 mg/l IBA, the number and length of regenerated shoots per culture being 6.07±0.39 and 5.84±0.65 cm, respectively. The best response to root induction (86.67%) was observed when shoots were transferred to ½ strength of gelled MS medium supplemented with 1.5 mg/l IBA within 16-24 days, with 13.60±1.76 roots per shoot unit. The well-rooted shoots were successfully acclimated in a mixture of soil, sand, and compost (1:1:1) with a survival rate of 88%. Jahangirnagar University J. Biol. Sci. 11(1 & 2): 31-40, 2022 (June & December)